From Access to Achievement: A PLS-SEM Analysis of Mobile Learning Engagement in Chinese Higher Education - Wu, Qinghao; Mohd Yusof, Norhayati; Zhang, Zhijun (International Journal of Interactive Mobile Technologies (iJIM), 2026)
This study investigates the adoption, effectiveness, and pedagogical impact of mobile learning applications on the academic development of college students in China. Specifically, it examines how perceived ease of use, perceived usefulness, instructor support, and access to mobile technology influence academic outcomes, with mobile learning engagement acting as a mediating factor. A quantitative research design was employed using survey data collected from 234 college students across various Chinese universities. Validated scales were adopted from prior studies to measure all constructs. SmartPLS 4.0 was used to analyze the structural relationships through partial least squares structural equation modelling (PLS-SEM). Results confirmed that perceived ease of use, perceived usefulness, instructor support, and access to mobile technology all have significant positive effects on students’ academic development. Furthermore, mobile learning engagement was found to mediate the relationships between these predictors and educational development, reinforcing its central role in digital learning environments. This study contributes to the growing body of literature on mobile learning by integrating elements from the technology acceptance model (TAM), Constructivist Learning Theory, and Engagement Theory. It offers practical and theoretical implications for educators, app developers, and policymakers aiming to foster meaningful student engagement and academic growth through mobile learning platforms.